Synergistic effect of formoterol and mometasone in a mouse model of allergic lung inflammation - Wyss, D (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Controversy still exists as to whether or not inhaled β (2)-adrenoceptor agonists and corticosteroids act synergistically in vivo. In this study, we have used a murine model of lung inflammation to study the synergistic effect of an inhaled β (2)-adrenoceptor agonists (formoterol) and an inhaled corticosteroid (mometasone). EXPERIMENTAL APPROACH: Actively sensitized mice were challenged with aerosolized ovalbumin, once a day, for three consecutive days. Three days after the last of the three challenges, a final allergen challenge was given. Allergen-induced increase in Penh was measured 4 h after the last challenge. A day after the last challenge, increased airway sensitivity to aerosolized methacholine was demonstrated and this was concomitant with an influx of inflammatory cells in the bronchoalveolar lavage fluids. KEY RESULTS: Mometasone (0.1 to 3 mg kg(−1)) given intranasally either an hour before or after the last allergen challenge, dose-dependently inhibited all parameters. When given intranasally either one or three hours after the last allergen challenge, but not an hour before, formoterol (1.5 to 150 μg kg(−1)) also dose-dependently inhibited most of the parameters to different degree. A synergistic effect on the allergen-induced increase in Penh was demonstrated for mometasone and formoterol given in combination, an hour after the challenge, at the following doses: mometasone/formoterol (in μg kg(−1)) 1/10, 1/100, 5/10, and 5/100. CONCLUSIONS AND IMPLICATIONS: Our results support the hypothesis that when given as a fixed combination, inhaled corticosteroid and β (2)-adrenoceptor agonist act synergistically in vivo.